The insights of smallholder farmers on special attributes of the genetically robust mule (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Desta TT, Teklemariam H, Mulugeta T. 2022. The insight of smallholder farmers on special attributes of the genetically robust mule. Biodiversitas 23: 3561-3566. A mule (Equus asinus X Equus caballus) is the offspring of a jack, a mature male donkey, and a mare, a mature female horse. Mule is the artifact of distant hybridization, and interspecific breeding has endowed mule with appreciable hardiness. In the history of humans, mule breeding represents a novel undying, and successful traditional biotechnology. This qualitative study reports the advantages and disadvantages of using mules as working and riding equid and insights of smallholder farmers on mule’s behavior and robustness. For most of the socio-economically important traits reported mule surpasses both the parental species, donkey and horse. This superiority is most likely associated with the genetic robustness of mules aroused from interspecific hybridization. It was reported that a mare mule is more intelligent, and quite the opposite, it is more aggressive than its male counterpart. Presumably, X-inactivation in distant hybrid animals like mules possessing heterologous X-chromosomes is suppressed; consequently, some of the X-chromosome genes might be escaped the inactivation process which makes the mare mule produce more of the protein products and surpass its male counterpart. The general sterility of mare mule may have also made it to invest virtually none in the costly task, nurturing of offspring. Mule's sterility and aggression make some of the community members develop negative insights. Regardless of this, the mule is highly appreciated for the various services it deliverstothe rural community.